Hubungan Persentase Lemak Tubuh dengan Nilai V̇O2 Maks Penerbang TNI AU - Widianto, Eri; Wibawanti, Retno; Mulijadi, Herman; Widyahening, Indah Suci; Isbaniah, Fathiyah; Sinabutar, Klara; Kekalih, Aria (Majalah Kedokteran Indonesia, 2023)
Introduction: Military pilots require good cardiorespiratory fitness due to the need to perform tasks in difficult and varied environmental conditions. Cardiorespiratory fitness is usually expressed in terms of maximal oxygen consumption (V̇O2 max). It is important to know the factors associated with V̇O2 max in order to maintain the fitness of Indonesian Air Force pilots. This study was conducted to assess the association between body fat percentage with V̇O2 max of Indonesian Air Force pilots.Methods: A cross-sectional study was conducted on active Indonesian Air Force pilots who carried out periodic medical examinations from October to November 2022 at Lakespra dr. Saryanto, Jakarta. The research subjects underwent body composition examinations using Bioelectrical Impedance Analysis (BIA), and V̇O2 max assessment was conducted using the Bruce protocol. The association between body fat percentage and V̇O2 max value was assessed by Pearson’s correlation test.Results: Of the 64 subjects analysed, the average value of V̇O2 max was 44.6±6.2 ml/kg/min and the average body fat percentage was 23.4±5.0 %. There is a significant correlation between body fat percentage and V̇O2 max. (r=-0.334; p=0.007)Conclusion: There is a significant negative correlation with moderate strength between the body fat percentage and the V̇O2 max of Indonesian Air Force pilots who carried out medical examination at Lakespra dr. Saryanto.